ก้าวสู่ประชาคมอาเซียนอย่างมั่นใจได้อย่างไร - ชิดนายี ศศิธร; วัฒนาธร อมรรัตน์ (Journal of Education and Innovation, 2013)
บทคัดย่อ การขับเคลื่อนประเทศเข้าสู่ประชาคมอาเซียนภายในปีพ.ศ.2558 บทบาทที่สำคัญของการศึกษาไทยโดยเฉพาะอุดมศึกษามีความสำคัญในการเตรียมความพร้อมให้กับบัณฑิตที่จะออกสู่ตลาดแข่งขันในเวทีอาเซียน ให้สามารถสื่อสารด้วยภาษาอังกฤษ การเรียนรู้อาเซียน สมรรถนะด้านวิชาชีพหรือทักษะเฉพาะ และทักษะด้านเทคโนโลยีสาสนเทศ ซึ่งการดำเนินงานต้องอาศัยความร่วมมือจากทุกภาคส่วน Abstract The driving force to achieve ASEAN community in 2015 is crucial role for Thai Nationparticularly in Higher Education. Thus universities have a mission to propose graduates who will bemore employable in ASEAN competitive market with English communicative competence, ASEANliteracy, vocational/technical competencies and also ITC literacy. This has to be fulfilled with acollaboration from all sectors.